Potential Analysis of Lemna sp. Extract as Immunostimulant to Increase Non-Specific Immune Response of Tilapia (Oreochromis niloticus) against Aeromonas hydrophila - Armando, Eric; Lestiyani, Ayu; Islamy, R. Adharyan (Research Journal of Life Science, 2021)
Lemna sp. is known to have several bioactive compounds and polysaccharide macromolecules that can function as immunomodulators to affect non-specific immune responses to increase the body's resistance to pathogens. This study aims to determine the potential of catfish eye extract as an immunostimulant by observing non-specific tilapia immune parameters. The extraction method used was 96% ethanol maceration for 2 days with a ratio of 1: 4. The experimental design used a Completely Randomized Design with 5 treatments (doses 0.2, 0.4, 0.6 mg/kg, control + and control -) and 3 replications. The non-specific parameters of immunity observed included total plasma protein (Bradford method), superoxide dismutase and lysozyme activity. The data obtained will be analyzed using ANOVA, if there is a significant difference, it will be further tested with Duncan Multiple. Range Test (DMRT). The results showed that the highest total plasma protein was found in treatment C (giving an extract of 0.3 mg/kg body weight) with an average total plasma protein after 12 days of maintenance of 4.99 g / dL. The extract dose of 0.3 mg/body weight showed a rapid decrease in SOD and increase Lysozyme activity.